2020
DOI: 10.3390/ma13102413
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Pressed Cups Producing Possibilities from Rolled Bimetallic Al-1050 + Cu-M1E Sheets

Abstract: Drawability tests of metal sheets are known and used as technological processes that allow assessing possibilities of plastic forming. One such test is the cupping test, which is very useful for examining thin sheets of both uniform and multilayer materials. In this work, a comprehensive analysis of the shaping of the bimetallic product Al–Cu (Al-1050 + Cu-M1E) was carried out. The research covers the entire production cycle, from explosive-welding, through asymmetric rolling (ASR) to deep drawing. The scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this study, aluminum alloy A1050 is chosen with a sheet thickness of t = 0.8 mm and material properties according to the supplier as shown in Table 1 . This material is a popular grade of aluminum alloy for the camera cover as moderate strength and formability are required [ 1 , 13 , 24 ].…”
Section: Numerical Simulation and Experimentsmentioning
confidence: 99%
“…In this study, aluminum alloy A1050 is chosen with a sheet thickness of t = 0.8 mm and material properties according to the supplier as shown in Table 1 . This material is a popular grade of aluminum alloy for the camera cover as moderate strength and formability are required [ 1 , 13 , 24 ].…”
Section: Numerical Simulation and Experimentsmentioning
confidence: 99%
“…Yanagimoto et al [ 74 ] observed the enhancement of the bending formability of type-420J2 stainless steel sheets when they are composed into a multilayer metallic sheet with type-304. Rydz et al [ 75 ] analyzed the shaping of bimetallic Al–Cu sheets in cup drawing tests. Kim et al [ 76 ] predicted the forming limit curve of a three-layer AA5182-O/polypropylene/AA5182-O (AA/PP/AA) sandwich sheet based on the Marciniak-Kuczynski (M-K) model and strain-rate potentials.…”
Section: Introductionmentioning
confidence: 99%
“…However, for bimetallic parts to operate properly, they have to be made of high quality materials that can be permanently joined over the entire contact surface. Depending on the intended use and required mechanical properties, bimetallic materials can be joined by bonding, adhesive bonding, press-fitting, or shrink-fitting [2][3][4][5][6]. Bimetallic materials for the production of machine parts that carry larger loads are typically welded or fusion-welded [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%